Analisis Organisasi & Pengembangan Kapasitas Kelembagaan Pada Sektor Wisata: (Studi di Dinas Pariwisata, Kebudayaan, Pemuda & Olahraga Kabupaten Pekalongan) - Tri Lestari Hadiati; Riyadi Riyadi (Public Service and Governance Journal, 2023)
The problems that exist in the Pekalongan Regency Tourism, Culture, Youth and Sports Office (Disporapar) on the one hand are problems in the organisational structure, especially in charge of Tourism, which has no sub-fields, even though the workload is very high. Another problem is that many tasks in the tourism sector have not been handled properly, such as the implementation of the licensing process and public services in the tourism sector, the implementation of qualifications and administration of tourism services, coordination and formulation of standards, norms and tourism promotion, and facilitation of tourism product development and the tourism business world and the creative economy in the tourism sector. On the other hand, it is a heavy responsibility for Disporapar to coordinate, communicate and socialise due to the low participation of the community to become "people aware of tourism".The purpose of the study was to analyse efforts to develop institutional capacity in public services in the field of tourism in Disporapar Pekalongan Regency. Analyse the factors that hinder and support capacity development efforts in public services in the field of tourism in Disporapar Pekalongan Regency. The data used are primary and secondary data. With data collection techniques using interviews, observation and documentation. Data analysis techniques through four stages that must be passed, namely information collection, data reduction, data presentation and drawing conclusions.Based on the results of the analysis of the above research, the conclusion is that first, the development of institutional capacity in coordinating public services in the tourism sector at the Pekalongan Regency Disporapar is not yet sufficient internally, such as budget improvement, improvement of organizational structure, recruitment of human resources apparatus, and provision of infrastructure facilities. Second, externally, there has been no development and improvement of tourism objects that are adequate for the consumption of local and foreign tourists in Pekalongan Regency. Thirdly, there is a lack of participation and awareness of the people to form "Rakyat Sadar Wisata" groups, but more people are not aware of tourism, so there is still "robbery" and destruction of tourist attraction facilities, illegal parking in tourist attraction areas, inadequate number and condition of tourist attraction facilities, and a lack of investors. However, there is a relief in the support from the Provincial and Central Governments as well as the availability of large areas of coastal, inland and mountainous land in Pekalongan Regency and the many potential natural resources in Pekalongan Regency that have not been utilised. However, there is a relief that there is support from the provincial and central governments as well as the availability of large areas of coastal, inland and mountainous land in Pekalongan Regency and there are still many potential natural resources in Pekalongan Regency that have not been utilised to create new tourism objects.